Mobilizing for nature in southern African community-based conservation policies, or the death of the local - (:unkn) unknown (My University, 2009)
Community-based natural resource management policies have been seriously criticized in the last few years. Detractors have focused either on the lack of local participation, or on the lack of ecological results. Using two of the earliest and most studied community-based natural resource management (CBNRM) initiatives in Africa (ADMADE in Zambia and CAMPFIRE in Zimbabwe), the article argues that such critics miss the actual stakes of community-based policies. These policies bring local communities into a global world, both in terms of practice and narrative. From this point of view, community-based policies must be viewed as long-term approaches to change in rural Africa, which will progressively make the local/global partition fuse into processes of continual social “mobilization”
Keywords: African Research